Risk factors associated with mortality and pathogen characteristics of bloodstream infection-induced severe sepsis in the pediatric intensive care unit: a retrospective cohort study - Jian Chen; Jian Chen; Haixin Huang; Ruichen Zhang; Yueqiang Fu; Chunmei Jing (Frontiers in Cellular and Infection Microbiology)
BackgroundBloodstream infection (BSI)-induced severe sepsis is a common cause of mortality, frequently resulting in septic shock and multiple organ dysfunction syndrome (MODS). This study aimed to analyze mortality risk factors and summarize pathogen characteristics associated with BSI-induced severe sepsis in the pediatric intensive care unit (PICU).MethodsThis retrospective study was conducted at a tertiary pediatric hospital between January 2015 and December 2023, encompassing children with BSI-induced severe sepsis in the PICU. Clinical characteristics, laboratory parameters, pathogen characteristics, and drug resistance profiles of the patients were collected. Clinical and laboratory indicators along with pathogen characteristics were summarized. Logistic regression analysis was employed to identify independent risk factors associated with 28-day mortality.ResultsA total of 192 patients with bloodstream infection (BSI)-induced severe sepsis were identified, with a 28-day in-hospital mortality rate of 36.98% (71/192). The incidence of septic shock (42.1% vs. 69%, P < 0.001) and AKI (14% vs. 31%, P = 0.005) was significantly lower in the survival group compared to the non-survival group. In multivariate analysis, independent risk factors for 28-day mortality were the pediatric sequential organ failure assessment (pSOFA) score (OR 1.176; 95% CI: 1.046-1.321, p = 0.007) and the P/F value (OR 0.994; 95% CI: 0.991-0.997, P < 0.001). Double organism growth was detected in 8 cultures, and a total of 200 pathogenic bacteria were isolated from all blood cultures. Of these, 110 strains (55.0%) were Gram-negative bacteria, 88 strains (44.0%) were gram-positive bacteria, and 2 strains (1.0%) were Candida albicans. The most commonly isolated pathogens were Staphylococcus aureus, Coagulase-negative Staphylococcus, and Escherichia coli. The detection rate of carbapenem resistance (CR) in Acinetobacter baumannii (66.7%) was higher than that in Pseudomonas aeruginosa (15.4%). The detection rates of extended-spectrum cephalosporin resistance (ECR) and fluoroquinolone resistance (FQR) in Escherichia coli (E. coli) were higher than those in Klebsiella pneumoniae.ConclusionIn the PICU, higher mortality was observed in children with BSI-induced severe sepsis who presented with elevated pSOFA scores and low P/F values. Acinetobacter baumannii exhibited the highest levels of CR and FQR, while Escherichia coli demonstrated the highest level of ECR.